Anthropometric parameters regarding the nutritional status of schoolchildren (2021)
Objective. This study assesses the anthropometric parameters concerning the nutritional status of and establishes the prevalence of excessive weight, obesity, and malnutrition among schoolchildren in an educational institution on Colombia’s northern coast. Materials and methods. A quantitative correlational research was conducted. The sample included 556 children aged between 6 and 11 years (310 boys and 246 girls). Their weight, height, BMI, and nutritional status were evaluated, and the BMI/age variable (Z-score)was studied to determine the nutritional categories of underweight, normal, and excess weight (overweight and obese) through a descriptive analysis and analysis of variance (ANOVA) using an unbalanced factorial design. Results. Thinness and obesity cases were reported, with 21.43% (119/556) of the students experiencing some kind of nutritional disorder. Although no statistically significant differences were observed between the gender factor levels, ANOVA showed that male students tend to move farther from the expectedZ-scores. Conclusion: The average Z-score of young students is usually closer to the expected score, whereas that of older students is farthest from expectation, in addition to showing greater variability between measures.